South Pacific [compact disc] : [original soundtrack recording]. - Rodgers, Richard, 1902-1979 (RCA, 2000)
South Pacific overture (3:01) -- Dites-moi (1:16) -- Cock-eyed optimist (1:42) -- Twin soliloquies / Some enchanted evening (5:49) -- Bloody Mary (1:53) -- My girl back home (1:39) -- There is nothin' like a dame (3:47) -- Bali Ha'i (3:49) -- I'm gonna wash that man right outa my hair (2:53) -- I'm in love with a wonderful guy (3:20) -- Younger than springtime (4:56) -- Happy talk (3:42) -- Honey bun (1:46) -- Carefully taught (1:13) -- This nearly was mine (2:09) -- Finale (2:59).